PERLINDUNGAN HUKUM BAGI PELAKU USAHA DALAM METODE TRANSAKSI COD CEK DULU - Fahrul Arifin; Fahrur Rosi; Sumriyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Legal protection must be strictly regulated in law to protect the unfulfilled rights of consumers and business actors in online buying and selling transactions. Business actors on the PT platform. Shopee Indonesia experienced non-fulfillment of its rights in the Cash On Delivery (COD) payment method, namely the right to receive payment according to the Cash On Delivery (COD) agreement. So regarding the conditions and exchange value of goods or services being bought and sold, they receive legal protection from consumer actions that do not comply with the agreement in Cash On Delivery (COD), which is stated in article 6 of law number 8 of 1999 concerning consumer protection (